Effect of segregation on particle size stability and SPS sintering of Li2O-Doped magnesium aluminate spinel. Issue 10 (August 2019) - Caliman, L.B.; Muche, D.; Silva, A.; Ospina R., C.A.; Machado, I.F.; Castro, R.H.R.; Gouvêa, D.
Abstract: Magnesium aluminate spinel (MAS) was prepared using the simultaneous precipitation method by varying the concentration of Li2 O from 0 to 5 mol%. No residual chlorine from the LiCl precursor was detected in the final powders while Li achieved the target concentration in all samples and contributed to stabilizing nanoparticles smaller than 10 nm. Li segregation to both interfaces (surfaces and grain boundaries) occurred and tended to be more pronounced at the grain boundaries stabilizing this type of interface during processing rather than surfaces. Spark plasma sintering (SPS) was used to consolidate the nanopowders into fully dense nanostructured pellets. The increase in Li content facilitated the sintering process and pore elimination occurred at 850–900 °C, a much lower temperature range as compared to conventional sintering (1650 °C). Samples containing 5 mol% Li sintered at 850 °C exhibited a medium grain size of ˜25 nm, microhardness of ˜24 GPa and ˜50% in-line optical transmission at the 800 nm.